Hubungan Pengetahuan Ibu dan Penyakit Infeksi dengan Status Gizi Balita di Posyandu Mawar A Kelurahan Mekarjaya, Kecamatan Sukmajaya, Kota Depok Tahun 2023 - Farida Sandra Melati; Ony Linda (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Nutrition is a very important part of the growth and development of toddlers, which is closely related to health and intelligence. The aim of this research is to determine the relationship between maternal knowledge and infectious diseases and the nutritional status of toddlers at Posyandu Mawar A, Mekarjaya Village, Sukmajaya District, Depok City in 2023. This type of research is quantitative analytical using a cross sectional design. The population in this study was 117 toddlers visiting Posyandu Mawar A, while the sample in this study was 75 toddlers at Posyandu Mawar A. The sampling technique used in this research was quota sampling. Data collection was carried out using primary and secondary data, using questionnaires and anthropometric measurements with the BB/U index. Data were analyzed univariately and bivariately using the chi square test. Univariate results show that 58.7% of toddlers have normal nutritional status, 57.3% of mothers have poor knowledge, 62.7% of toddlers do not have infectious diseases. The results of the bivariate test showed that there was a relationship between the variables of knowledge (p = 0.025) and infectious diseases (p = 0.000) with the nutritional status of toddlers. Therefore, education such as counseling is needed to increase mothers' knowledge and improve the nutritional status of toddlers.